Total electron ionization cross-sections for molecules of astrochemical interest - Zhou, W; Wilkinson, L; Lee, J; Heathcote, D; Vallance, C (Taylor and Francis Group, 2019)
We describe a newly upgraded instrument for measuring absolute total electron ionization cross-sections over the energy range from 0 to 300 eV, and present cross-sections for nine previously unstudied molecules, as well as several small molecules for which comparison data is available. The measured cross-sections are compared with the predictions of the BEB model, and show reasonable agreement with the model, albeit peaking at higher electron energies than predicted by the model. We show that the maxima in the cross-sections follow an additivity model, such that the molecular cross-sections can be expressed as a sum over contributions from the constituent atoms. These contributions have been determined from a global fit to the data for all molecules studied, and allow maximum cross-sections to be predicted for molecules that have not been studied to date. We demonstrate the expected correlation between the maximum ionization cross-section and the molecular polarisability, and show that the atomic contributions to the cross-section show a similar dependence on the atomic polarisability. The observed correlation can be used as an alternative method for predicting unknown maximum cross-sections.